Vulnerability analysis of buildings under seismic loading - Wang, Yingbiao. (2008)
In this study, the vulnerability of a typical rectangular HDB high-rise residential building is investigated in transverse and longitudinal directions. The building capacity will first be obtained by the pushover analysis method, and then the capacity spectrum method is used to obtain the building response.